Table of Content - -, (Journal of Educational and Psychological Sciences, 2024)
Table of Content1. Requirements for implementing the Green School's initiative in Public Education Schools in JeddahMrs. Fatimah Talal Masrahi, Mrs. Norah Obaid Alshareef, Prof. Najah Mohammed Alsaigh2. Inclusion of Twenty-First Century Skills in the Books of Digital Skills for Fourth Elementary School in Saudi ArabiaMrs. Haya Ali Alqurini, Prof. Najwa Atyan Al-Muhammadi3. The Degree to Which the Teachers Who Won the Queen Rania Al-Abdullah Award for Educational Excellence Possess and Practice Twenty-First Century Skills from Their Point of ViewMrs. Mohammed Musa Al-Salamat, Dr. Jehad Al-Momeni4. Spiritual intelligence and its relationship to psychological flow as predictors of psychological quality of life for secondary school teachers in RiyadhMrs. Hessa Fahd Al-Quraini, Dr. Siham Mahji Al-Mutairi5. The locus of control and its relationship to psychological anxiety among Individuals Recovering From COVID-19 in MadinahMrs. Roaa Talal Sagga6. The Psychological Impact of Bullying on Children’s Personalities and Cognitive Development: A Case Study of Saudi ChildrenDr. Uhuud fahad Alassaf
Keywords: Journal of Educational and Psychological Sciences